2022
DOI: 10.3389/fnut.2022.775557
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationship Between Dietary Patterns in Early Pregnancy and Maternal/Infant Health Outcomes in a Chinese Cohort

Abstract: BackgroundStudies assessing links between maternal diet and pregnancy outcomes have focused predominantly on individual nutrients or foods. However, nutrients are typically consumed in combinations of foods or beverages (i.e., dietary patterns). Taking into account the diet as a whole appreciates that nutrient absorption and metabolism are influenced by other nutrients and the food matrix.ObjectiveThe aim of this study was to investigate the relationship between dietary pattern consumption in early pregnancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…PW has been negatively correlated with a maternal fast food-like dietary pattern ( 49 ) while another study found low PW in mothers with low adherence to a Mediterranean-like dietary pattern ( 50 ). Here, higher diet quality (based on the HEI-2015 score) was associated with lower PW.…”
Section: Discussionmentioning
confidence: 99%
“…PW has been negatively correlated with a maternal fast food-like dietary pattern ( 49 ) while another study found low PW in mothers with low adherence to a Mediterranean-like dietary pattern ( 50 ). Here, higher diet quality (based on the HEI-2015 score) was associated with lower PW.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection will include information from the women on environmental, health and lifestyle factors at study visits 1, 2, 3 and 5–10 (tables 1 and 2). Information to be collected from the women over the three prenatal visits will include past and present medical and health history, pregnancy and sociodemographic factors (age, education, occupation, family), along with lifestyle factors such as smoking and alcohol consumption 21 25. Clinical assessments will be conducted at each visit, with a range of measurements (weight, height, waist circumference and blood pressure) recorded.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Temporal Distribution of Research: The analysis of the studies on the impact of nutrition during pregnancy on the neurodevelopment of offspring found that they were conducted at different stages of pregnancy. Specifically, some studies focused on the first and second trimesters (12)(13)(14)(15)(16), somespanned the second and third trimesters (11,(17)(18)(19)(20)(21) and other encompassed the first and third trimesters.…”
Section: Studymentioning
confidence: 99%